ANALISIS DISIPLIN KERJA PEGAWAI PADA DINAS PENGELOLAAN KEUANGAN DAN ASET (DPKA) KABUPATEN ROKAN HULU - -, Syahrial (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
Syahrial, 1025096, 2015, the analysis of employee discipline in the financial services and asset management (DPKA) Rokan Hulu district, Anal, Supervisor I Welven Aida, S.Pd, M.Pd dan Supervisor II Asrori, S.Pd, MM.The aim of this research is to know what the factors the level of discipline of employees working at the office of finance and asset management (DPKA) Rokan HuluDistrict, held in may to October 2014, population of this research is all employees of finance and asset management (DPKA) Rokan Hulu which amounted to 107 people,69 civil servant (PNS) and 38 Honorary and sample of this research is all of populations, data analysis techniques using qualitative descriptive technique which data in the formof information in a narrative description connected to other data in order to obtain a new picture or strengthen already existing picture.Based on the results of the study found the factor analysis of employee discipline in the financial services and asset management (DPKA) Rokan Hulu district, include breachof discipline, sanctions imposed, employee welfare, employee participation and the exemplary of leaders. From the data processing questioner obtained the mostdominant factors that affect the discipline is 1& 2 = Penulis Penanggung Jawab exemplary leader, 69-34 percent fromemployees giving good ratings. In order to that is not the dominant factor of 5 factors that affect the discipline is variable breach of discipline only 51,87 percent of employees who claimed firmness against disciplineviolation performing well.In this research writer giving suggestion where is to improve employee discipline, leadership in this case the head ofdepartment of financial and asset management (DPKA) to be more focused sanctions with firmness against disciplineviolations to employees, leader restrict the activities of his subordinates as well as control of discipline and impose sanctions according to the rules applicable.